Друг детства - Драгунский Виктор Юзефович (Малышам, 2005)
Экземпляры: ф.19 (ретро) / Инвентарный номер: 41470 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 72 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44